Globalized: The Imperativeness of Intercultural Competence for International Public Relations Practices - Adamu, Mohammed Alhaji; Auwal, Alhassan (Kashere Journal of Politics and International Relations, 2023)
Globalisation aided by the new communication technologies makes the world virtually smaller and brings different people and cultures closer together. Thus, it makes communication and interactions much faster and easier though at first value. The main function of International Public Relations, IPR is to build, sustain and improve organization’s reputation by fostering mutual understanding and relationship between an organization and it’s publics across national boundaries. More so, most have diverse cultural institutions and inclinations, for maximum benefit. Central to public relations is communication, which is, in many ways, being influenced by culture. This paper aims at closing the literature gap on centrality of local culture in international public relations practice across the globalised world. The paper reviews and discusses the role of culture in the success or failure of International (intercultural) Public Relations practice. It highlights how multinationals, perhaps lured by the notion of globalised or global culture, adopt centralized approach to international public relations practice. It posits that several International public relations campaign fail due to disregard to the culture of the local countries of operation. It argues that though an IPR practitioner may not know everything about various culture of the local countries, he/she must be conversant with cultural practices and institutions that affect their business practice which in turn must be aligned with PR practice to record success.